DISCECTOMY IN SINGLE LEVEL LUMBAR DISC DISEASE - Raja, Riaz Ahmad; Khemani, Vash Dev; Lakhair, Manzoor Ali; Khan, Shahbaz Ali (Journal of Ayub Medical College Abbottabad, 2012)
Background: There is a controversy regarding the treatment of lumbar disc herniation. Most of patients with lumbar disc herniation and radiculopathy improve with rest and medicine. Lumbar disc surgery gives rapid relief to the patients with severe root pain in legs. This study was conducted to see the risks and benefits of surgery in single level symptomatic lumbar disc disease. Methods: This prospective study was conducted in Department of Neurosurgery, Liaquat University of Medical and Health Sciences, Jamshoro during 2007-2009. Patients with severe leg pain, positive straight leg raising, and confirmed disc extrusion on imaging were included and conventional open discectomy was performed. Patients were followed up for one year after the surgery. Results: Forty-five patients were operated for lumbar root pain due to a single disc. Most common disc involved was L4-5 and discectomy was performed. Recurrence of disc occurred in 4 patients. Conclusion: Proper selection of patients is necessary for excellent postoperative results in back surgery. Failed back surgery continues to rise with high rate of lumbar spine surgery as many patients are selected inappropriately. Keywords: Lumbar disc herniation, open discectomy, backache